Sleep homeostasis in lizards and the role of the cortex - Sena Hatori; Sho T. Yamaguchi; Riho Kobayashi; Kazuki Okamoto; Zhiwen Zhou; Koki T. Kotake; Futaba Matsui; Hiroyuki Hioki; Hiroaki Norimoto (Proceedings of the National Academy of Sciences, 2025)
Slow-wave sleep (SWS) and rapid eye movement sleep are the two primary components of electrophysiological sleep (e-sleep) in mammals and birds. Slow waves in the cortex not only characterize SWS but are also used as biological markers for sleep homeostasis, given their rebound after sleep deprivation (SD). Recently, it has been reported that the Australian dragon Pogona vitticeps exhibits a two-stage sleep pattern in the dorsal ventricular ridge (DVR), which includes a homologue of the mammalian claustrum (CLA). It remains unclear whether reptilian e-sleep, which has been characterized by activity outside the cortex, compensates for sleep loss, as observed in mammals. We here report a significant rebound in the local field potential (LFP) after 7 h of SD. Meanwhile, the mean bout length of each sleep state remained unaffected. We further investigated a possible role of the cortex in e-sleep regulation and homeostasis in Pogona and found that although a corticotomy had no obvious effect on the LFP features of baseline sleep, it abolished LFP power rebound in the CLA/DVR after SD. These findings suggest that e-sleep homeostasis is a common feature in amniotes and that the cortex is involved in regulating activity rebounds in reptiles and mammals.